Creating a Hierarchical Model of Software Reliability for Educational Software - Gurov, Valery V. (Computer Tools in Education, 2020)
Currently, various types of educational software are widely introduced into the educati?onal process of all higher education institutions, from lecture support tools, practical and laboratory classes to assessing students’ knowledge. In addition to programs developed and distributed (for a fee or free of charge) by large companies, each University has a wi?despread practice when a number of such programs are written by relatively small teams of their own developers, who take into account the existing methods of teaching certain disciplines in this university and are able to respond quickly to constantly changing requi?rements for the educational process.In the latter case, developers face a two-fold task. On the one hand, they need to create the necessary product as quickly as possible, but on the other hand, it must meet the necessary quality requirements, including reliability. Various reliability models are used to evaluate this parameter. In particular, the Mills model can be used at the early stages of creating a software module. One of its di?sadvantages in this area is that in order to assess the reliability of the result given by this model, it is desirable to know the expected initial number of errors in the program.This value can be obtained using a simple intuitive software reliability model that does not require a complex log of monitoring the progress of testing and does not require complex calculations. The paper shows how it is possible to combine the use of these models into a single hierarchical model that can be effectively used in the subject area under consideration.
Keywords: educational software, software reliability, Mill’s error seeding model, simple intuitive software reliability model